“ESTUDIO DOCTRINARIO Y JURÍDICO DE LA POLÍTICA CRIMINAL DE LA PENA DE MUERTE, EN LOS DELITOS QUE LESIONEN LOS BIENES JURÍDICOS DE LA INTEGRIDAD E INDEMNIDAD DE LAS NIÑAS/OS EN EL ECUADOR - Ríos Ríos, Katherine Elizabeth (2019)
This thesis titled "DOCTRINARY AND LEGAL STUDY OF THE CRIMINAL POLICY OF THE DEATH PENALTY, IN CRIMES THAT INJURY THE LEGAL PROPERTY OF THE INTEGRITY AND INDEMNITY OF THE GIRLS IN ECUADOR", its motivation is to show that In recent years there has been a social reality that is coming out of the hands of State social control and its legal system, since according to the research that occurs in our country, we are facing high statistics since 2014 until June 27, 2018, according to data from the Ministry of Education received 4,111 complaints of sexual violence, of which 2,274 were committed outside the school environment and 1,837 occurred within it. Every time it is important to take into account the high degree of delinquency that we find in our country against children. Situations that are worrisome causing a great social commotion. However, these crimes deserve analysis because they continue to be committed despite the fact that these sanctions are established in our legal system, although it is true that several crimes committed against children have been sanctioned. The general objective of the present study is to conduct a doctrinal and legal study of the criminal policy of the death penalty for those crimes that damage the legal rights of the integrity and indemnity of children in Ecuador, being of a descriptive nature since It describes the various aspects that lead to the problem, as well as methods such as scientific, inductive, deductive, analytical, exegetical and comparative, the techniques that were applied were surveys and interviews aimed at legal professionals 5 knowledgeable about the problematic, taking as sample 30 lawyers, where the importance of analyzing drastic sanctions such as the Death Penalty is a sanction applied in some countries in the world, taking into account that in our country the death penalty can not be applied since the Constitution of the Republic of Ecuador prohibits it, as well as the International Treaties and Agreements to which is subscribed. However, I consider it appropriate to apply life imprisonment for those who commit these crimes and thus ensure the intimidating effect of punishment as general and special prevention, thereby protecting the rights of girls and boys by creating a safer environment for its development and development, having to corroborate that the sanctions established in our legal system have not been sufficient to prevent this type of crime and therefore it is not possible to achieve respect for the rights of children, the integral development of the same and on the other the rehabilitation of the offender, in this way it is necessary to create action guides for institutions where children, the family, and society are involved.